The Didache in context : essays on its text, history, and transmission - Jefford, Clayton N. (Novum Testamentum, Supplements, 1995)
The Didache in Context contains an intriguing look into the background of the Didache, exploring the influence of the text upon the development of early Christianity. It offers an insightful collection of essays that have been gathered from the research efforts of numerous biblical and patristic scholars from around the world. The book seeks to explore questions that relate to the composition of the text itself, the history of the role and function of the Didache within early Christian circles, and the influence of the manuscript upon early Christian traditions and trends of thought. In addition to the numerous, individual investigations that are featured here, the collection includes a fresh translation of the text in English and a comprehensive, up-to-date bibliography of literature on the Didache.